KAJIAN KEAMANAN PENGOPERASIAN PUBLIC TRANSPORT TINJAUAN TERHADAP KEKUATAN RANGKA BODY BUS - Sudiro, B. M (Jurnal Sains dan Teknologi Indonesia, 2010)
In order to meet the safety and security of the public transportation, design specification of construction body bus or bus frame structures should have an appropriate structural strength and comply with standard design including the safety factor and selection of material besides static and dynamic testing of the part of body bus. It is also realized that a bus carrying passengers have to give secure to the passengers also driver.The fact that a technology concerning with metal works industry to fascinate the body bus industry is being used in small and medium body bus industries. Eventhough some of the body bus industries having designer background but it may still develop their design capability by using advanced technology. Materials to be used for designing parts of body bus should meet specific requirements. It could be understood that safety and security during operation is a priority matter.Lifetime of the bus parts or components may be predicted through the dynamic or fatigue test from its parts or components. Palmgren and Miner hypothesis may be used in dynamic ratio decision in connection with fatigue test application up to the fraction of the parts or components being tested.